(untitled) - Ohkawa, Kazuhi (Tokyo, 1989)
This book consists of the following two part: The phrases of development economic development in historical perspective, semi-industrialization, technology, productivity, and employmant; Major factors and activities technology borrowing and human resources, capability, education, and utilization, industrial policy.
Keywords: Economic development,Economic policy,Developing countries; Economic policy; Japan,Japan